Synthesis, Characterization, Molecular Docking, and In Silico ADME Study for Some New Different Derivatives for Succiniohydrazide - Asmaa A. Maryoosh; Oday H. R. Al-Jeilawi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2025)
Many studies have found effective oral influenza virus inhibitors based on an aryl benzoyl hydrazide scaffold and antiviral. This study aims to prepare a new series of derivatives containing succinohydrazide as a precursor. In the first step, after synthesis of their precursor, it has been prepared di benzoyl succinohydrazide using a two-step process that involved reacting (o,m,p)-chloro benzoic acid with thionyl chloride to obtain freshly prepared substituted benzoyl chloride derivatives that were then reacted with succinohydrazide, or by a second method, directly reacting substituted benzoyl chloride with succinohydrazide to give benzoylsuccinohydrazide derivatives. After that, different derivatives were prepared involving the reaction of succinohydrazide with substituted benzene sulphonyl chloride, benzyl chloride, and phenacyl chloride. FTIR, 1HNMR, and 13CNMR spectra have been used to verify the structures of newly synthesized compounds. The Swiss ADME method with boiled egg prediction was used to analyze its pharmacokinetic properties. Then, genetic optimization of linkage docking (GOLD) was used in theoretical studies to investigate the binding mechanism of the protein-ligand produced with the protein (1SA0). Among all synthesis compounds, compound 2b has excellent results compared with colchicine and can be considered a good anti-bacterial against Escherichia coli and an anti-breast cancer drug.